2006
DOI: 10.1111/j.1365-2265.2006.02508.x
|View full text |Cite
|
Sign up to set email alerts
|

GH replacement does not increase the risk of recurrence in patients with craniopharyngioma

Abstract: Forty-one subjects received GH replacement. Nine of them did not have follow-up imaging during GH therapy and were not included in the statistical analyses. The remaining 32 (22 males/10 females) received GH for a mean period of 6.3 +/- 4.6 years (median 5.1, range 0.8-22); 21 started during childhood (13 of them continued after the achievement of final height with an adult dose) and 11 during adult life. The mean duration of their follow-up (from surgery until last assessment) was 10.8 +/- 9.2 years (range 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 39 publications
2
53
2
2
Order By: Relevance
“…The majority of studies in survivors of previous neoplasia, particularly brain tumours, have not indicated an association between GH treatment and increased tumour recurrence or occurrence of second neoplasms (26,27,28,29,30,31). Two analyses from the Childhood Cancer Survivor Study (CCSS) indicated that GH treatment is associated with an increase in the relative risk (RR) of second neoplasms in childhood cancer survivors (32,33); these findings are supported by earlier analyses from HypoCCS (34).…”
Section: Introductionsupporting
confidence: 63%
“…The majority of studies in survivors of previous neoplasia, particularly brain tumours, have not indicated an association between GH treatment and increased tumour recurrence or occurrence of second neoplasms (26,27,28,29,30,31). Two analyses from the Childhood Cancer Survivor Study (CCSS) indicated that GH treatment is associated with an increase in the relative risk (RR) of second neoplasms in childhood cancer survivors (32,33); these findings are supported by earlier analyses from HypoCCS (34).…”
Section: Introductionsupporting
confidence: 63%
“…Additional characteristics of the included studies are shown in Table 1. As shown in table, seven of the selected studies obtained seven or more scores, which indicated that the study quality was relatively higher [5][6][7][14][15][16][17][18][19][20][21][22]; whereas, other studies with relatively lesser scores were considered of lower quality [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…A total of four studies [7,21,22,26] in our meta-analysis estimated the risk of craniopharyngioma. Figure 4 shows the forest plots for craniopharyngioma recurrence/progression in individuals with and without GHRT.…”
Section: Ghrt For Craniopharyngiomamentioning
confidence: 99%
“…In a study reporting the results of prospective imaging in 28 consecutive patients with craniopharyngioma and adult-onset GHD, an apparent increase in tumour volume was found in one subject 6 years after the commencement of GH (76). In another study, 32 patients with a mean age of 17.6 years at diagnosis of craniopharyngioma and with GH replacement for a mean period of 6.3 years were compared with 53 patients who had not received GH but otherwise with a similar tumour and treatment characteristics and follow-up period (77). During the period of observation, 4 patients treated with GH and 22 not receiving GH developed tumour recurrence (77).…”
Section: Hypothalamic-pituitary Tumoursmentioning
confidence: 99%
“…In another study, 32 patients with a mean age of 17.6 years at diagnosis of craniopharyngioma and with GH replacement for a mean period of 6.3 years were compared with 53 patients who had not received GH but otherwise with a similar tumour and treatment characteristics and follow-up period (77). During the period of observation, 4 patients treated with GH and 22 not receiving GH developed tumour recurrence (77). Thus, in conclusion, data published so far are reassuring and there is, to date, no evidence that GH replacement increases the recurrence rate of craniopharyngiomas in children or adults.…”
Section: Hypothalamic-pituitary Tumoursmentioning
confidence: 99%